Finite element study of the properties and response of 3D printed lattice structures - Lam, Wei Han (Nanyang Technological University, 2020)
This report covers the finite element study of 3D-printed lattice structure. 1D beam analysis is conducted on finite element software, Abaqus. BCC unit cell is selected as the basis of the 4x4x5 unit cell lattice. In the first part of the report, analyses are performed for 20% compression of lattice in the elastic and plastic deformation region. The causes for mismatch results with experimental results are explained and the author attempts to improve the strut stiffness through the increased thickness, increased Young modulus, and fixed rotation of the nodes. In the second part of the report, the ductile damage response of the lattice from one stress triaxiality point to multiple stress triaxiality points is studied. The lattice response to different velocities and mass scaling are investigated and observations from simulations are made. Lastly, the report sums up the parameters explored and outlines some of the possible future developments to this project.